Inovasi Alat Pemotong dan Pemisah Kulit Kedelai untuk Meningkatkan Efisiensi Produksi pada UMKM Setia Tempe (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2025)
Tempeh is a traditional food with high nutritional value with high market demand, but many UMKM such as Setia Tempe still face obstacles in the production process, for the breaking of 30 kg of soybeans takes 20 minutes, especially at the stage of separating soybean skins which is still done manually. This process takes 20 minutes and two workers to process 30 kg of soybeans which causes low efficiency and high operational costs. This study aims to design a soybean skin breaker and separator tool that can increase production capacity up to 80 kg / hour. This research method is carried out by designing a tool that has the function of breaking and separating soybean skins. This design considers ergonomic aspects and production capacity, with the aim of increasing the production capacity of soybean skin breaking and separation and increasing employee/operator work productivity. As a result, the process becomes faster with only 22.5 minutes for 30 kg of soybeans and is operated by one person, it can increase time and labor efficiency by up to 45.75%. In addition, the processing capacity increases to 53.4 kg per cycle. This tool provides a strategic solution to increase the productivity and competitiveness of MSMEs in the tempeh processing sector.